Integrated assessment of indoor and outdoor ventilation in street canyons with naturally-ventilated buildings by various ventilation indexes. (February 2020) - Yang, Xia; Zhang, Yong; Hang, Jian; Lin, Yuanyuan; Mattsson, Magnus; Sandberg, Mats; Zhang, Ming; Wang, Kai
Abstract: The integrated assessments of indoor and outdoor ventilation are still rare so far. As a novelty, this paper aims to quantify the influence of street aspect ratios (building height/street width, H/W = 0.5–5) and window sizes (1 m × 1 m, 1.5 m × 1.5 m) on indoor-outdoor ventilation in two-dimensional streets with single-sided naturally-ventilated buildings. Numerical simulations with RNG k-ε model are validated against experimental data and the grid independence are tested as well. Air change rates per hour ( ACH, h −1 ) are adopted for assessing indoor-outdoor ventilation by mean flows ( ACH mean ) and turbulent fluctuations ( ACH turb ) respectively. Age of air( τ ), purging flow rate ( PFR ) and its corresponding ACH PFR are used to evaluate overall ventilation capacities. Shallower streets experience better indoor-outdoor ventilation. Outdoor ACH PFR drop from 14.69 to 17.55 h −1 to 3.96–3.97 h −1 as H/W rises from 0.5 to 3. In extremely deep canyon ( H/W = 5), two-counter-rotating vortices produce much smaller velocity at low-level regions ( U/U ref 10 −3 -10 −5 ), resulting in small ACH PFR for outdoor ( 0.76–0.91 h −1 ) and indoor in 1–13th floors ( 0.03–0.61 h −1 ). When H/W = 0.5–1, leeward 5–6th floors experience smaller ACH PFR (e.g. 1.13–1.40 h −1 as H/W = 1) than the other floors (e.g. 1.54–9.52 h −1 as H/W = 1). Particularly, as H/W = 2–3, leeward-side indoor ACH PFR in the middle floors (except the first and top two floors) are nearly constants ( 1.02–1.69 h −1 ) and much smaller than windward-side ACH PFR ( 1.41–4.35 h −1 ) which increase toward upper floors. Besides, the smaller window size reduces indoor ACH PFR by 19.38% 88.28%, but hardly influences outdoor ventilation. Moreover, both outdoor and indoor ACH PFR are greater than ACH mean but smaller than ACH mean + ACH turb . Although further investigations are still required, this paper provides an insight and scientific foundation on integrated indoor-outdoor ventilation evaluation with various effective ventilation indexes. Highlights: It provides an insight to assess the coupled indoor and outdoor ventilation by CFD. ACH by mean flows ( ACH mean )/turbulence ( ACH turb )/purging flow rate ( ACH PFR ) are adopted. Outdoor ACH PFR are from 18 h −1 to 4 h −1 as H/W = 0.5 to 3 and only 0.8–0.9 h −1 as H/W = 5. Indoor ACHs is smaller than outdoor, and window sizes hardly affect outdoor ACHs. Both outdoor/indoor ACH PFR are greater than ACH mean but smaller than ACH mean + ACH turb .